Outcomes and factors associated with mortality among Traumatic Brain injury patients admitted to the Intensive care units of comprehensive specialized hospitals in the Amhara Region, 2022. A Multi-center retrospective cross-sectional study - Mengistu Abebe Messelu; Temesgen Ayenew; Aster Tadesse Shibabaw; Gebrehiwot Berie Mekonnen; Asnake Gashaw Belayneh; Tiruye Azene Demile; Belay Alemayehu Getahun; Ashenafi Fekad Getahun; Tadesse Miretie Dessie (Elsevier, 2023)
Background: Traumatic Brain Injury (TBI) is a substantial cause of morbidity and mortality across all age groups. However, there is a paucity of research on outcomes and associated factors of mortality among patients with TBI admitted to the Intensive Care Unit (ICU) in low-income countries, including Ethiopia. Objective: To assess the outcomes and associated factors of mortality among patients with TBI admitted to ICU in comprehensive specialized hospitals in Amhara region, Ethiopia. Methods and materials: Institutional-based cross-sectional study was conducted among 241 patients with TBI and selected by using simple random sampling method. Data collected by using Kobo collect was exported into SPSS version 25 for analysis. An Adjusted Odds Ratio (AOR) with 95% Confidence Intervals (CI) was computed, and variables with a P-value < 0.05 were considered statistically significant. Result: From a total of 241 TBI patients admitted to the ICU, 50.2%, 39.4%, 5.4% and 5% were improved, died, transfer out and left against medical advice, respectively. The presence of complications (AOR = 4.53, 95% CI: 1.87, 11.00), Glasgow Coma Scale (GCS) score < 9 (AOR = 4.97; 95% CI: 1.76, 14.06), comorbidity (AOR = 3.35, 95% CI: 1.35, 9.10), co-existing injury (AOR = 3.31, 95% CI: 1.44, 7.60), and being on mechanical ventilation (AOR = 2.81, 95% CI: 1.18, 6.70) were all significantly associated with mortality. Conclusions: The overall mortality of patients with traumatic brain injury who admitted to the ICU was high. GCS score < 9, presence of complications, comorbidity, co-existing injury, and being on mechanical ventilation were significantly associated with mortality. Special attention should be given to those TBI patients with lower GCS, comorbidity, co-existing injury, and being on mechanical ventilation.